(untitled) (Journal of the College of Education for Women, 2019)
Howard Gardner (1983), in his book (Frames of mind) has confirmed that intelligence which has been measured in the traditional way as well as the short answers and paper and pencil tests do not evaluate intelligence fully. As intelligence represents a certain intellectual ability requires a set of problemsolving skills and enable the individual to create an effective product when it is appropriate in the cultural context in which the individual lives as well as the intelligence isa dynamiccharacterthat is not fixedat birth. Intelligence can grow and develop by proper learning. (Gardner) has identified seven types of intelligences and added another type of intelligences later becameeight. As seen by (Gardner), that all kinds of intelligences are self-sufficient, but it is linked to the other consistencies, and it does not work in isolation from the cultural and social context, and this theory has presented a new concept of a scientificnatureremoves it fromthe abstract nature.